Solidarność związkowa. O zaangażowaniu niemieckich związków zawodowych na rzecz NSZZ ?Solidarność? = The support of German trade unions for NSZZ Solidarność - Świder, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The events that took place in Poland were accompanied by the interest of foreign trade unions,including the Confederation of German Trade Unions (DGB), from the very first days of the unrest. The first official statement supporting Solidarność was published on 25 August 1980. The actions by DGB were based on the policy of ?quiet help? for Polish opposition outlined by the German government and SPD.
Keywords: NSZZ Solidarność; związki zawodowe; Polska - a Niemcy - 20 w.